328 A Propensity-Based Analysis of the Use of Prothrombin Complex Concentrate Prior to Emergent Neurosurgical Procedures. (August 2016) - Agarwal, Prateek; Ramayya, Ashwin G.; Abdullah, Kalil G.; Nayak, Nikhil; Lucas, Timothy H.
Abstract : INTRODUCTION: Reversal of anticoagulation is required to mitigate the risk of intracranial bleeding before urgent neurosurgical procedures. New pharmacological agents, such as multifactor prothrombin complex concentrate (PCC; Kcentra), promise rapid efficacy but may raise the probability of thrombotic complications above vitamin K infusion or administration of fresh frozen plasma (FFP). In this study, we examined the rate of thrombotic complications in neurosurgical patients who received either PCC or FFP and Vitamin K before undergoing urgent surgery. METHODS: Sixty-three consecutive patients who received anticoagulation reversal for urgent neurosurgical procedures were identified between 2008 and 2014 at a level I trauma center. They were divided into 2 cohorts based on reversal method, either PCC (n = 28) or FFP/Vitamin K (n = 35). The rate of thrombotic complications within 72 hours of reversal was compared using a 2-sample t test. To minimize selection bias, a multivariate propensity score-matching analysis was then used to identify a control group of FFP patients most similar to patients in the PCC group based on age, sex, trauma, altered mental status, and preexisting heart failure. RESULTS: Thrombotic complications were uncommon but not rare in this neurosurgical population, occurring in 8.3% of treated patients (3/63). There was no difference in thrombotic complication rate between groups, 7.14% (2/28; PCC group) vs 2.86% (1/28; FFP group; P = ns). Propensity matching analysis verified this finding after controlling for any selection bias. CONCLUSION: Thrombotic complications in neurosurgical patients requiring rapid reversal at a level I trauma center are uncommon but not rare. New pharmacological agents have similar rates of thrombotic complications as FFP. In this limited sample, use of PCC did not pose a significant increase in risk compared with FFP in the management of intracranial bleeding.